Efficacy and safety of empagliflozin at different doses in patients with type 2 diabetes mellitus: A network meta‐analysis based on randomized controlled trials. (20th September 2021) - Wu, Qian; Liu, Miaowen; Fang, Zige; Li, Chenxi; Zou, Fang; Hu, Lei; Zhang, Wenxiong
Abstract: What is Known and Objective: As an oral hypoglycaemic drug that significantly reduces cardiovascular risk, empagliflozin is often used in patients with type 2 diabetes mellitus (T2DM). However, the dosage and administration of empagliflozin are still controversial clinically. To determine the most appropriate dose, we performed this network meta‐analysis. Methods: We identified randomized controlled trials (RCTs) about empagliflozin from eight databases. We analysed the pharmacodynamics, adverse effects (AEs), and pharmacokinetics of empagliflozin at different doses. Results: We identified 8264 articles, of which 23 RCTs with 10518 patients were included. Regarding haemoglobin A1c (HbA1c) and fasting plasma glucose (FPG), high‐daily doses (10, 25, 50 mg) were significantly better than low doses (1, 2.5, 5 mg). For total AEs, there was a dose‐response trend in which safety decreased with increasing doses. According to SUCRA sequencing, the order for lowering HbA1c was 25 > 50 > 10 > 5 > 1 mg, for lowering FPG was 50 > 25 > 10 > 5 > 2.5 > 1 mg and for safety was 1> 5 > 10 > 25> 2.5 > 50 mg. When considering HbA1c, FPG and total AEs, we performed a hierarchical cluster analysis and network meta‐analysis to find that 25 mg performed best among different doses, which was more significant after long‐term use (≥ 12 weeks). Pharmacokinetic parameters exhibited significant dose‐response relationships. What is New and Conclusion: High‐daily doses (10, 25, 50 mg) had better efficacy than low doses (1, 2.5, 5 mg). When considering HbA1c, FPG and total AEs, 25 mg performed best among the different doses in patients with T2DM. Abstract : This network meta‐analysis is the first to assess the appropriate dosage and administration of empagliflozin. The results suggested that High doses (10, 25, 50 mg) had better efficacy than low doses (1, 2.5, 5 mg). When considering HbA1c, FPG and total AEs, 25 mg performed best among the different doses.